PENERAPAN METODE WEIGHTED PRODUCT (WP) DAN ELIMINATION ET CHOIX TRANDUISANT LA REALITÉ (ELECTRE) DENGAN PEMBOBOTAN ENTROPY MENGGUNAKAN GUI MATLAB (Studi Kasus: Pemilihan Hero Terkuat Arena of Valor) - Sukanianto, Eko Adyan; Sugito, Sugito; Rahmawati, Rita (Jurnal Gaussian, 2018)
Arena of Valor (AOV) is a mobile game published by Garena in Indonesia. There will be 5 players in each team, selecting a hero to play in the game. By selecting the strongest hero each role can help facilitate team to strategize the composition of heroes that will be used to achieve victory. Weighting each criteria and selecting the strongest hero also become a consideration to control the game to be stable and balanced by the developer. The alternatives are all hero from each role (Tank, Warrior, Assassin, Mage, Archer and Support), while the criterias are skill effect points, maximum HP (Health Points), physical attack, physical defense, movement speed and HP recovery every 5 seconds. In this study, the writer uses WP and ELECTRE methods to select the strongest hero with Entropy weighting method. This study produce a Matlab GUI that can be used to facilitate computational selection. The results show that the strongest hero in AOV are Grakk (Tank), Astrid (Warrior), Ormarr (Warrior), Murad (Warrior/Assassin), Lauriel (Mage/Assassin), The Joker (Archer) and Alice (Support). While the criteria with the highest weighting is the skill. Keywords: AOV, Garena Indonesia, WP, ELECTRE, Entropy, GUI Matlab